Orienting fatigue cracks using contact acoustic nonlinearity in scattered plate waves - Wang, Kai (2020)
Targeting quantitative delineation of nonlinear scatterers in elastic media and undersized fatigue cracks in particular, the present study is dedicated to investigation, from analytical, numerical, and experimental perspectives, of the underlying mechanism of interaction between guided ultrasonic waves (GUWs) and 'breathing' fatigue cracks - a representative nonlinear scatterer type. Under the modulation of probing GUWs, a 'breathing' crack scatters GUWs, in which the crack-triggered contact acoustic nonlinearity (CAN) is embodied. Analytical modeling demonstrates that the extracted CAN manifests unique scattering patterns associated with the crack slant, on which basis the crack can be oriented, without requiring reference to baseline signals. Experimental validation corroborates analytical prediction, in which an embryonic fatigue crack in an aluminum plate waveguide is oriented accurately and visualized in a pixelated image.